Smart technologies - Worden, K. (World Scientific, 2003)
A general introduction to intelligent or smart materials, systems and machines. Presented in understandable and non-mathematical terms, it is for anyone who is interested in future developments in these fields or who needs to be briefed on the current status of these interdisciplinary technologies. The intended audience comprises physicists, engineers, materials scientists and computer scientists of all levels, from undergraduates to post-doctoral practitioners.
Keywords: Technological innovations.; Smart structures.; Smart materials.; elektronické knihy; electronic books